2015
DOI: 10.1155/2015/329570
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Magnetic Properties of Rare‐Earth Metals Doped ZnO Monolayer

Abstract: The structural, electronic, and magnetic properties of rare-earth metals doped ZnO monolayer have been investigated using the first-principles calculations. The induced spin polarization is confirmed for Ce, Eu, Gd, and Dy dopings while the induced spin polarization is negligible for Y doping. The localizedfstates of rare-earth atoms respond to the introduction of a magnetic moment. ZnO monolayer undergoes transition from semiconductor to metal in the presence of Y, Ce, Gd, and Dy doping. More interestingly, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…On the other hand, in RE elements, the peripheral 4f electrons are localized, having indirect exchange interactions among 5d or 6s conduction electrons. Therefore, RE elements can be expected to have a high total magnetic moments per atom owing to its high orbital momentum than that of TMs [ 113 , 251 ]. Various TMs such as Fe, Co, Cr, Mn, and Ni, and RE elements such as Eu, Tb, La and Gd have been exploited as dopants for creating doped ZnO NPs DMS.…”
Section: Use Of Doped Zno Nps In the Biomedical Fieldmentioning
confidence: 99%
“…On the other hand, in RE elements, the peripheral 4f electrons are localized, having indirect exchange interactions among 5d or 6s conduction electrons. Therefore, RE elements can be expected to have a high total magnetic moments per atom owing to its high orbital momentum than that of TMs [ 113 , 251 ]. Various TMs such as Fe, Co, Cr, Mn, and Ni, and RE elements such as Eu, Tb, La and Gd have been exploited as dopants for creating doped ZnO NPs DMS.…”
Section: Use Of Doped Zno Nps In the Biomedical Fieldmentioning
confidence: 99%
“…Experimentally, Deng et al [41] synthesized a ZnO ML by reactive deposition of Zn on Au (111), which confirmed the existence of a ZnO ML graphite-like structure. Tan et al [42] investigated the structural, electronic, and magnetic properties of RE metals (RE = Y, Ce, Eu, Gd, and Dy) doped ZnO ML using the DMol 3 package. The ZnO ML with Ce, Eu, Gd, or Dy was magnetic, but Y-doped ZnO ML was a nonmagnetic semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports, on the other hand, have already shown that intrinsic defects and impurities can readily give rise to magnetism in ZnO allotropies, including monolayer, graphitic layers, thin films, nanowires and nanoribbons [19][20][21][22][23][24][25][26][27][28][29]. For instance, nonmetal (C, B, N, and K)- [27,29] and rareearth metal (Ce, Eu, Gd, and Dy)-doped ZnO monolayer [28] exhibits magnetic instability via first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports, on the other hand, have already shown that intrinsic defects and impurities can readily give rise to magnetism in ZnO allotropies, including monolayer, graphitic layers, thin films, nanowires and nanoribbons [19][20][21][22][23][24][25][26][27][28][29]. For instance, nonmetal (C, B, N, and K)- [27,29] and rareearth metal (Ce, Eu, Gd, and Dy)-doped ZnO monolayer [28] exhibits magnetic instability via first-principles calculations. Moreover, it has been shown by both exper imentally [20,22,26] and theoretically [19,23,24] that the Zn vacancy induces ferromagnetism in either thin films [20,22,24,26] and graphitic layers [19,23] of ZnO without the need of magnetic impurities.…”
Section: Introductionmentioning
confidence: 99%